Collaborative Governance in Tourism Law Enforcement: A Study on the Implementation of the ASOCA Strategy in Jakarta - John C.E. Nababan; Muh. Ilham; Mansyur Achmad; Yudi Rusfiana (Khazanah Sosial, 2025)
Law enforcement in Jakarta’s urban tourism industry faces complex challenges, ranging from licensing violations and labor exploitation to environmental degradation and weak tourism security oversight. This study aims to analyze the effectiveness of collaborative governance in tourism law enforcement through the interaction between state and community actors. The research design employs a qualitative approach, collecting data through semi-structured interviews with key stakeholders (Tourism Office, Civil Service Police Unit/Satpol PP, Police, Pokdarwis, and FKPM), field observations at strategic tourism locations in Jakarta, and analysis of policy documents and institutional reports. The analysis draws on the collaborative governance framework and is further enriched by the ASOCA strategy (Ability, Strength, Opportunities, Culture, Agility) to evaluate inter-agency collaborative capacity. The findings indicate that inter-agency forums, digital reporting, joint operations, and community legal education have improved supervision effectiveness and fostered public ownership of tourism regulations. However, these efforts remain limited by regulatory fragmentation, resource disparities, weak coordination SOPs, and bureaucratic resistance to community participation. The study’s original contribution lies in the application of the ASOCA strategy as an institutional analytical tool in the context of urban tourism governance—a methodological innovation that broadens the understanding of plural policing and community-based law enforcement. This study recommends institutionalizing cross-actor task forces, introducing performance-based participatory incentives, and strengthening digital reporting systems as action plans to develop a responsive, collaborative, and sustainable tourism governance framework.